Recovery of molybdenum, nickel and cobalt by precipitation from the acidic leachate of a mineral sludge. Issue 17 (1st September 2016) - Vemic, M.; Bordas, F.; Comte, S.; Guibaud, G.; Lens, P. N. L.; van Hullebusch, E. D.
ABSTRACT: The objective of this study was to investigate the recovery potential of molybdenum (Mo), nickel (Ni) and cobalt (Co) from synthetic and real acidic leachate of a mineral sludge from a metal recycling plant by sulfide precipitation. The operational parameters (metal sulfide (M/S) ratio 0.1–1, agitation speed 0–100 rpm, contact time 15–120 min and pH 1–5) were optimized in batch conditions on synthetic metal leachate (0.5 M HNO3, Mo = 101.6 mg L −1, Ni = 70.8 mg L −1, Co = 27.1 mg L −1 ) with a 0.1 M Na2 S solution. Additionally, recovery of the target metals was theoretically simulated with a chemical equilibrium model (Visual MINTEQ 3.0). The optimized Na2 S precipitation of metals from the synthetic leachate resulted in the potential selective recovery of Mo at pH 1 (98% by modeling, 95% experimental), after simultaneous precipitation of Ni and Co as sulfide at pH 4 (100% by modeling, 98% experimental). Metal precipitation from the real leachate (18 M H2 SO4, Mo = 10, 160 mg L −1, Ni = 7, 080 mg L −1, Co = 2, 710 mg L −1 ) was performed with 1 M Na2 S, and resulted in a maximal Mo recovery at pH 2 (50%), while maximal recoveries of Ni and Co were observed at pH 4 (56% and 60%, respectively). Real leachate gave a lower metals recovery efficiency compared with synthetic leachate, which can be attributed to changes in the pH, nature of leachant, co-precipitation of Zn and competition for S 2− ions. GRAPHICAL ABSTRACT: